(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2023)
A study was conducted on community structure, ecology, and conservation issues of the avifauna of two human-dominated landscapes in a lower Ganges Madhukhali Upazila, under the Faridpur district during the COVID-19 pandemic period. Direct field observations were made from April 2020 to March 2021. In total, 109 species of birds belong to 18 orders, and 49 families were observed, with a total count of 5,453 individuals. Resident bird species (93 species, 85.32%) dominant in the study area, whereas the migratory species were only 16 (14.68%). The highest number of bird species (93 species, 85.32%) with the highest number of individuals (n=3171, 58.15%) was observed in Beleswar (rural site) area. Shannon diversity index value (H=3.89, Ds= 0.9724) was higher in the rural site than Madhukhali municipal area (urban site). In the winter season, the highest number of bird species (95 species, 87.15%) with the highest number of individuals (n=2303, 42.23%) was observed. Among micro-habitats, trees, particularly the native tree species, were the preferable sites for bird nesting, foraging, and roosting. Among birds, Acridotheres tristis was the most abundant species (n=316, 5.79%) in the study area, and an uneven distribution of species in the community structure was observed. The abundance of birds shows that 59 (54.12%) species were very common, 8 (7.33%) common, 9 (8.25%) uncommon, and 33 (30.27%) rare. Among the bird species, Ichthyophaga ichthyaetus was categorised as Near Threatened (NT), and the rest are Least Concerned (IUCN Bangladesh 2015). Illegal hunting of birds, especially waterbirds, is the major threat in the rural site. Preparing a proper management plan based on the baseline data is essential for protecting of avian diversity in the study area. J. Asiat. Soc. Bangladesh, Sci. 48(1-2): 53-66, June-December 2022